2022 Joint European Conference on Networks and Communications &Amp; 6G Summit (EuCNC/6G Summit) 2022
DOI: 10.1109/eucnc/6gsummit54941.2022.9815602
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Received Signal Strength in Industrial IoT Distributed Massive MIMO Systems

Abstract: The Fifth Generation (5G) of wireless networks introduced native support for Machine-Type Communication (MTC), which is a key enabler for the Internet of Things (IoT) revolution. Current 5G standards are not yet capable of fully satisfying the requirements of critical MTC (cMTC) and massive MTC (mMTC) use cases. This is the main reason why industry and academia have already started working on technical solutions for beyond-5G and Sixth Generation (6G) networks. One technological solution that has been extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(60 reference statements)
0
0
0
Order By: Relevance
“…In [120], a novel UL detection scheme named quasi-LMMSE is introduced, utilizing only the MRC fronthaul signals. In [121], the received signal strength in an industrial Internet of things (IoT) context with mMIMO is studied. The authors compared the macro-diversity and signal spatial diversity performance of traditional mMIMO with different D-mMIMO setups, such as RS, and found that D-mIMO can provide higher average channel gains.…”
Section: Developments On Radio Stripe Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…In [120], a novel UL detection scheme named quasi-LMMSE is introduced, utilizing only the MRC fronthaul signals. In [121], the received signal strength in an industrial Internet of things (IoT) context with mMIMO is studied. The authors compared the macro-diversity and signal spatial diversity performance of traditional mMIMO with different D-mMIMO setups, such as RS, and found that D-mIMO can provide higher average channel gains.…”
Section: Developments On Radio Stripe Technologymentioning
confidence: 99%
“…Uplink (UL) NLMMSE-based [115] OSLP-based [116] RZF-based [119] Quasi-LMMSE-based [120] Clustered-based [123] Cluster-MMSE-based [137] MRT-based [118] Spatial Diversity Performance [121] Exploration [126] Integration [127] Outage Probabilities [122] LDPC codification [136] Comparison with CF [16] Comparison with LIS [138] Low-pass [124,125] Joint Positioning and synchronization with ML [133] APS to improve PE [135,139] SO power optimization [128] BO power optimization [129] BO APS to improve SE/LB [131] MO power optimization [130]…”
Section: Resource Allocation (Ra)mentioning
confidence: 99%
“…Due to the above, radio stripes technology is attractive for supporting energy-efficient (and sustainable) networks. Applications are numerous, e.g., to: i) facilitate high spatial multiplexing and low EC in indoor communications [209], ii) increase the coverage and end-to-end PTE of RF-WET [22], [210], and iii) support ultra-reliable low-latency communications in industrial IoT networks [211]. In general, although the last few years have witnessed significant advances in this technology (e.g., see [212]- [214] and references therein), more advanced/efficient resource allocation schemes, circuit implementations and prototypes, and distributed processing architectures to avoid costly signaling between the antenna elements, still pose open research challenges.…”
Section: Radio Stripesmentioning
confidence: 99%